2008
DOI: 10.1203/pdr.0b013e31816d9130
|View full text |Cite
|
Sign up to set email alerts
|

Augmented and Accelerated Nephrogenesis in TGF-β2 Heterozygous Mutant Mice

Abstract: Several members of the transforming growth factor-␤ (TGF-␤) superfamily play key roles in kidney development, either directly or indirectly regulating nephron number. Although low nephron number is a risk factor for cardiovascular and renal disease, the implications of increased nephron number has not been examined due to the absence of appropriate animal models. Here, using unbiased stereology we demonstrated that kidneys from TGF-␤2 heterozygous (TGF-␤2 ϩ/Ϫ ) mice have approximately 60% more nephrons than wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
48
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(51 citation statements)
references
References 36 publications
(39 reference statements)
3
48
0
Order By: Relevance
“…41 Furthermore, Tgf␤2 heterozygous mice are characterized by increased ureteric branch length and nephron number, consistent with a physiologic inhibitory effect of Tgf␤2 in vivo. 31 Combined, these results support a role for TGF␤2 inhibiting ureteric branching in ␤-cat…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…41 Furthermore, Tgf␤2 heterozygous mice are characterized by increased ureteric branch length and nephron number, consistent with a physiologic inhibitory effect of Tgf␤2 in vivo. 31 Combined, these results support a role for TGF␤2 inhibiting ureteric branching in ␤-cat…”
Section: Discussionmentioning
confidence: 64%
“…Interestingly, those genes in the WNT pathway encoded WNT inhibitors including Dickkopf 1 (Dkk1), WNT inhibitory factor 1 (Wif1), and secreted frizzledrelated protein (sFrp) ( Table 5). Because previous studies demonstrated that Dkk1 and Tgf␤2 inhibit ureteric branching and nephrogenesis, respectively, 31,32 we proceeded with further analysis of these effectors. Upregulation of Tgf␤2 and Dkk1 was verified using quantitative real-time PCR on mRNA isolated from ␤-cat GOF-UB and WT kidneys (P ϭ 0.038) ( Figure 4J).…”
Section: Gof-ubmentioning
confidence: 99%
“…7,10,19,22,23 Previous studies have shown that inactivation of Bmp4 disrupts the structural and functional organization of the kidney and lower urinary tract. 16 To specifically investigate the role of canonical Smaddependent TGF-b superfamily signaling in the development of the lower urinary tract, we have used the Tbx18-Cre transgene to mediate the inactivation of Smad4, the common Smad indispensible for the transcriptional responses of TGF-b superfamily signaling, in the ureteral mesenchyme.…”
Section: Discussionmentioning
confidence: 99%
“…Total volume was calculated with the Cavalieri Principle. 35,36 Glomerular volume was estimated with the physical dissector/fractionator principle as previously described 37,38 where sections were projected on an unbiased 2 ϫ 2-cm grid at a final magnification of ϫ298.…”
Section: Stereologic Estimation Of Total Kidney and Glomerular Volumesmentioning
confidence: 99%